Economic and growth performance of Boer-type goats when fed corn dried distiller's grains with solubles and corn gluten feed as a substitute for soybean meal - Brown, Rachel E.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
Global goat population has increased by 34% in the past 10 years; the US population has increased by 211% in the past 15 years (NASS, 2002 and 2017). Thus, there is increased need for economical goat diets; however, there is limited information on the impact of different ingredients on goat growth performance. The objective of this study was to determine the growth and economic incentive for replacing soybean meal with corn dried distiller’s grains with solubles (DDGS) and corn gluten feed (CGF) in Boer-type goats. Seventy-five Boer-type goats (average BW of 26.9kg±0.2, ~70 d of age) were used. Goats were fed five treatments of diets varying in levels of DDGS and CGF replacement for 35 d. Diets were isocaloric and isonitrogenous but varied in protein source: 1) 100%SBM, 2) 100%DDGS/0%CGF, 3) 66%DDGS/33%CGF, 4) 33%DDGS/66%CGF, 5) 0%DDGS/100%CGF. Pen was used as the experimental unit; each treatment had 5 pens with 3 randomly-allotted goats/pen in a completely randomized design. Goats and feeders were weighed weekly to determine ADG, ADFI, and F/G. Data were analyzed using GLIMMIX procedure of SAS (v.9.4, Cary, NC), with 0.05 as the accepted alpha. There were no observed effects (P>0.05) of dietary treatment on final BW, ADG, ADFI, or G:F. However, goats fed diets with corn co-products instead of SBM reduced feed cost/goat (P=0.0008) and feed cost/kg of feed by approximately $0.04 for goats fed corn co-products. There was no evidence of feed cost/kg of gain being affected (P>0.05) by diet. These results suggest that based on growth performance and economic incentive, there may be benefit to replacing SBM with DDGS or CGF in Boer-type goat diets.
Keywords: Spring 2019